2019
DOI: 10.25248/reas.e1262.2019
|View full text |Cite
|
Sign up to set email alerts
|

Ocorrência de sintomas depressivos em paciente idosos com doença arterial periférica

Abstract: Objetivo: investigar a ocorrência de sintomas depressivos em idosos com doença arterial periférica (DAP) internados num hospital filantrópico em Aracaju.  Métodos: estudo descritivo, observacional, transversal realizado no Serviço de Cirurgia Vascular de um hospital terciário durante o período de novembro de 2018 a abril de 2019.  Foram incluídos pacientes com idade igual ou superior a 60 anos, com diagnóstico de DAP e que responderam aos questionários sociodemográfico e escala de depressão geriátrica de 15 it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 3 publications
1
1
0
2
Order By: Relevance
“…This is an elevated prevalence compared to studies conducted in other places in Brazil, which reported prevalence rates of 50% in São Luís (MA), 46.51% in Maceió (AL), 41.4% in the Federal District (DF), 27.6% in Aracaju (SE), 22% in rural areas of Minas Gerais (MG), and 16.4% in Florianópolis (SC). [21][22][23][24][25][26][27] However, it is similar to the rate found by Mota et al 28 who studied occurrence of depressive symptoms in elderly patients with peripheral arterial disease, finding a 61.8% rate of depression.…”
Section: Discussionsupporting
confidence: 87%
“…This is an elevated prevalence compared to studies conducted in other places in Brazil, which reported prevalence rates of 50% in São Luís (MA), 46.51% in Maceió (AL), 41.4% in the Federal District (DF), 27.6% in Aracaju (SE), 22% in rural areas of Minas Gerais (MG), and 16.4% in Florianópolis (SC). [21][22][23][24][25][26][27] However, it is similar to the rate found by Mota et al 28 who studied occurrence of depressive symptoms in elderly patients with peripheral arterial disease, finding a 61.8% rate of depression.…”
Section: Discussionsupporting
confidence: 87%
“…Trata-se de uma prevalência elevada quando comparada a estudos nacionais conduzidos em diferentes locais do Brasil, os quais apresentaram prevalências de 50% em São Luís (MA), 46,51% em Maceió (AL), 41,4% no Distrito Federal (DF), 27,6% em Aracaju (SE), 22% na zona rural de Minas Gerais (MG) e 16,4% em Florianópolis (SC) [21][22][23][24][25][26][27] . Porém, é semelhante ao encontrado por Mota et al 28 que, estudando a ocorrência de sintomas depressivos em paciente idosos com doença arterial periférica, encontrou uma taxa de depressão de 61,8%.…”
Section: Resultsunclassified
“…Conclusion: We conclude that the regular practice of physical activity is of utmost importance in strengthening, muscular strength and balance, thus helping the performance of alds and the aivd, giving the elderly a greater security in their autonomy and prevention of falls. (MOTA et al, 2019).…”
Section: Bioquímica Da Ureia E a Síndrome Urêmicamentioning
confidence: 99%